(untitled) - T L Isenhour (New York, 1981)
The central objective of this book is to provide an algebraic refresher in a chemistry context. It is divided into three parts. Part one is devoted to basic mathematical skills and drill problems. Part two introduces some chemical concepts basic to the regular chemistry course. Problems - followed by answers - are included to demonstrate the application of concepts. Part three consists of five appendices - two diagnostic quizzea, review of mathematics and nomenclature, and answers to problems from the easy sections
Keywords: chemistry - study and teaching